A process-based dynamic model for succinic acid production by Actinobacillus succinogenes: regulatory role of ATP/ADP balance - Salucci, Emiliano; Cartenì, Fabrizio; Giannino, Francesco; de Alteriis, Elisabetta; Raganati, Francesca; Mazzoleni, Stefano (Frontiers in Microbiology, 2025)
IntroductionSuccinic acid is an important chemical compound for biotechnological productions, being used as a basic platform to produce many industrial products in major business applications. It can be produced as fermentation end-product of anaerobic metabolism of different bacterial species, among which Actinobacillus succinogenes is largely used. Modeling microbial metabolic processes in controlled bioreactor systems is recognized as a useful tool to optimize growth conditions aimed at maximizing yield.MethodsA novel model is presented based on System Dynamics approach in which the maintenance of the ATP/ADP balance is introduced as a key regulatory process of A. succinogenes metabolism.Results and discussionModel simulations accurately reproduce microbial growth and succinic acid production in anaerobic batch cultures at different initial glucose concentrations. Results reveal that the main limitations to maximal succinic acid production are glucose uptake restrictions and energy homeostasis costs (ATP/ADP balance) of the microbial population. The process-based modeling approach effectively describes the main metabolic processes and their regulation, providing a useful tool to define working conditions and overcome the criticalities of the SA fermentation process.